Stabilization of Catalytically Active Cu+ Surface Sites on Titanium–Copper Mixed‐Oxide Films1. Issue 21 (9th April 2014) - Baber, Ashleigh E.; Yang, Xiaofang; Kim, Hyun You; Mudiyanselage, Kumudu; Soldemo, Markus; Weissenrieder, Jonas; Senanayake, Sanjaya D.; Al‐Mahboob, Abdullah; Sadowski, Jerzy T.; Evans, Jaime; Rodriguez, José A.; Liu, Ping; et al.
Abstract The oxidation of CO is the archetypal heterogeneous catalytic reaction and plays a central role in the advancement of fundamental studies, the control of automobile emissions, and industrial oxidation reactions. Copper‐based catalysts were the first catalysts that were reported to enable the oxidation of CO at room temperature, but a lack of stability at the elevated reaction temperatures that are used in automobile catalytic converters, in particular the loss of the most reactive Cu+ cations, leads to their deactivation. Using a combined experimental and theoretical approach, it is shown how the incorporation of titanium cations in a Cu2O film leads to the formation of a stable mixed‐metal oxide with a Cu+ terminated surface that is highly active for CO oxidation.